Climate Variability and Soil Moisture Status in the KhadoKholaWatershed in Eastern Terai Region of Nepal - Mandala, Umesh Kumar (Economic Journal of Nepal, 2015)
The present research has attempted to analyze the impact of climate vriability on soil moisture status. The analysis has been based on standard Thornthwaite water balance approach and Krishna and Mukthar Singh’s index of soil moisture and twenty-seven years of historical rainfall and temperature data. During last 27 years, mean annual daily temperature in the watershed has increased by 2.2°C more than national average. The trend of mean annual daily and minimum temperature were found increasing at rate of 0.005°C & 0.02°C per year respectively where as mean maximum temperature was decreased at rate of 0.024°C. Similarly, annual total rainfall as a source of supply of water has been decreasing at the rate of 20.91 mm every year higher than national level of 0.82mm. Similarly potential evapotranspiration (PET) as a demand of water has been increasing at rate of 6.68 mm per year. As a result of decreased rainfall and increased PET, availability soil moisture was found declining at the rate of 1.85 percent annually and 50 percent of the years under study was found as moisture deficit. Such declining trend of soil moisture draws the attention of management strategic measures such as dry farming, crop shift and additional irrigation facilities for the sustainable crop production required for ever increasing population in the watershed. The Economic Journal of Nepal, Vol. 35, No. 3, July-September 2012 (Issue N0. 139)